2015
DOI: 10.1589/jpts.27.1401
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatigue and stress among Korean police officers

Abstract: [Purpose] This study investigated factors that affect the health of police officers by analyzing job stress, psychosocial stress, and fatigue faced by police officers in order to provide basic data for the efficient management of police officers and future comparative research. [Subjects and Methods] Police officers admitted to the National Police Hospital from March to May 2013 were surveyed to investigate their degree of stress. The questionnaire consisted of 4 areas related to patient characteristics: gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…These concerns were further built upon by another cross-sectional study which identified individual shift work tolerance as being an important factor influencing fatigue development48 ) ; when comparing Dutch police officers based on a subjective self-perception as intolerant, medium-tolerance and tolerance to shift work, the primarily related variables included sleep quality, need for recovery and fatigue48 ) . Another study involving Korean police officers also sought to investigate the variables impacting police officer health by studying job and psychosocial stress, as well as fatigue49 ) . There were no relationships found between officers’ fatigue and their age group, marital status, education level, service length or rank, however ordinary and shift working officers were found to be at a high risk of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns were further built upon by another cross-sectional study which identified individual shift work tolerance as being an important factor influencing fatigue development48 ) ; when comparing Dutch police officers based on a subjective self-perception as intolerant, medium-tolerance and tolerance to shift work, the primarily related variables included sleep quality, need for recovery and fatigue48 ) . Another study involving Korean police officers also sought to investigate the variables impacting police officer health by studying job and psychosocial stress, as well as fatigue49 ) . There were no relationships found between officers’ fatigue and their age group, marital status, education level, service length or rank, however ordinary and shift working officers were found to be at a high risk of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…work injuries, violence, shift work, lack of support, job demands, fatigue, long working hours, etc. (Berg et al , 2005; Houdmont and Randall, 2016; Nelson and Smith, 2016; Seok et al , 2015). Stress negatively affects mental and physical health of police officers resulting in various consequences such as increased risk of metabolic syndrome, dyslipidaemia, obesity and hypertension, poor sleep quality, alcohol and drug abuse, job dissatisfaction, absenteeism, reduced productivity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This research presented has focused on fatigue and satisfaction which have previously been identified as problem areas for police (28,30,31,48). While these are two factors with known associations to psychosocial health, other associations need to be studied.…”
Section: Insert Tablementioning
confidence: 99%
“…Previous research into the health and wellbeing of police has identified several factors that negatively affect the psychosocial health of police and could potentially be incorporated into an occupation specific JDCS model. Those most frequently cited are shift work (27) and harassment and threats of violence (9) Shift work has been associated with a number of adverse health outcomes in a variety of professional groups, including higher levels of work stress (4,8,25), increased risk of cardiovascular disease (17,20,25), fatigue (21,(28)(29)(30)(31) and on-duty injury (3). Shift work in the police force has specifically been associated with a higher incidence of work-related stressors (27), poor sleep quality (5,32,33), increased systolic blood pressure (34) and a higher risk of workplace injury (1,35).…”
Section: Introductionmentioning
confidence: 99%